Tolerance of pineapple cultivars to natural flowering induction in the state of Mato Grosso - Debora; Krause, Willian; Padilha de Freitas, Angélica; Castro Silva, Dayane; Dallacort, Rivanildo; Fenner, William (Comunicata Scientiae, 2024)
Natural flowering in pineapple crops can cause significant economic losses to growers, resulting in uneven fruiting, which hinders phytosanitary operations and the scaling of fruit harvest. The objective of this work was to evaluate the tolerance of eight pineapple cultivars to natural flowering induction in Tangara da Serra, Mato Grosso, Brazil. The cultivars BRS-Ajuba, BRS-Imperial, BRS-Vitoria, Gigante-de-Tarauaca, IAC-Fantastico, Jupi, Perola, and Smooth-Cayenne were evaluated. Planting was carried out in May of 2018, in a randomized block design, with five replications and 20 plants per plot. Plant height, D-leaf length, and percentage of induced plants were evaluated. The surveying period of plants naturally induced was between May and September 2019. In this period, the plants were between 12 and 16 months of age, with adequate D-leaf lengths and plant heights for the occurrence of flowering induction. There were days with night-time temperatures below 15 °C; the lowest photoperiod was in June. The cultivars Smooth-Cayenne, BRS-Imperial, and IAC-Fantastico were tolerant to the natural induction, which resulted in uneven fruiting, causing losses to growers.